Empathy as a culturally embedded therapeutic practice: A qualitative case study in Sundanese counseling contexts - Diswantika, Noviana; Rusmana, Nandang; Suherman, Uman; Qurbi, Abdullah (Educenter : Jurnal Ilmiah Pendidikan, 2025)
Empathy in counseling serves not only an interpersonal skill but also as a therapeutic practice shaped by cultural values. In Sundanese society, empathy is manifested through the values of silih asih (compassion), silih asah (grooming), and silih asuh (nurturing), which emphasize harmony, caring, and collective responsibility in social relationships. However, the understanding of empathy in counseling practice is still dominated by a Western perspective that underrepresents the dynamics of empathy in collectivist cultures. This study aims to examine empathy as a therapeutic practice rooted in Sundanese cultural values in the context of counseling in Indonesia. The study employed a qualitative case study design, collecting data through interviews, observations, and document analysis with therapists and clients in community counseling services, schools, and private practice. Thematic analysis identified four main themes: empathy as a basis for building trust; the expression of empathy through Sundanese cultural values; challenges in maintaining empathy, such as over-identification and emotional exhaustion; and strategies for sustaining empathy through supervision and peer support. The findings indicate that empathy is both a universal therapeutic mechanism and a culturally constructed practice. This study emphasizes the importance of integrating local cultural values into counseling practices that are responsive to the Indonesian context.